PENETAPAN KADAR FLAVONOID TOTAL DARI EKSTRAK ETANOL DAUN ANDALIMAN (Zanthoxylum acanthopodium DC.) - Yettri Simarmata; Cut Masyithah Thaib; Siti Nurbaya; Martha Uli Oktavrina Rajagukguk (Jurnal Farmanesia, 2017)
Flavonoids are a class of polyphenolic compounds that have an antioxidant effect by donating hydrogen atoms and linking them with metal ions. Most flavonoids are found in plants. One of the plants that contain lots of flavonoids is andaliman (Zanthoxylum acanthopodium DC). The purpose of this study was to determine the compounds contained in the Andaliman leaf and to determine the total flavonoid content of the Andaliman leaf extract. The type of research conducted was descriptive, including identification of plant material, collection of plant material, phytochemical screening, and examination of total flavonoids with visible ultraviolet spectrophotometry. Samples were taken from LobuSiregar village, Siborong-Borong, North Tapanuli. Andaliman leaf extract (Zanthoxylum acanthopodium DC) was obtained by the maceration method using 96% ethanol. Determination of total flavonoid content was carried out by the colorimetric method. The results of phytochemical screening showed the presence of alkaloids, flavonoids, tannins, and steroids. Determination of total flavonoid content calculated as quercetin with the regression equation y= 0.03278 X + 0.04086, and r = 0.99825. The measurement results of the total flavonoid content of the ethanol extract of Andaliman leaves were 39.65 ± 0.08 mg QE/g.